Proximate and antioxidant analysis of steamed cake made from flour of green bean sprout (Vigna radiata) and ambon banana peel (Musa paradisiaca var. sapientum (L.) Kunt.) as main ingredients - Ulmillah, Aulia; Hardiyanti, Ninda; Kuswanto, Eko (Univeritas Papua, 2023)
Steamed cake is a type of cake that is enjoyed by all ages, both children and adults. This cake is usually made from wheat flour. Wheat flour causes dough to rise due to the gluten content. The use of excessive flour can be harmful to health. One alternative effort to replace wheat flour is to combine green bean sprout flour and Ambon banana peel flour. This study aims to determine the antioxidant level, the protein, fat, water, ash, and carbohydrate levels in steamed cakes made from green bean sprout flour and Ambon banana peel flour. This type of research is experimental. Antioxidants were analyzed using the DPPH method, protein was analyzed using the Kjeldahl method, and fat was analyzed using the Soxhlet method. The research results showed that the antioxidant activity in green bean sprout flour was 360.30 ppm which was classified as very weak, banana peel flour was 165.58 ppm which was classified as weak. The highest protein content was in sample T0 at 7.01%, the highest fat content was in sample T0 at 0.77%, the highest water content was in sample T2 at 43.95%, the highest ash content was in sample T3 at 1.15%, and the highest carbohydrate content was in sample T0 at 53.44%.